Can you help me to simplify this algebraic expression? (-2)/(x^2-1)+(x)/(x+1} -(1)/(x-1)

Urijah Estes 2022-07-20 Answered
Can you help me to simplify this algebraic expression?
How can I simplify this algebraic expression?
2 x 2 1 + x x + 1 1 x 1
You can still ask an expert for help

Expert Community at Your Service

  • Live experts 24/7
  • Questions are typically answered in as fast as 30 minutes
  • Personalized clear answers
Learn more

Solve your problem for the price of one coffee

  • Available 24/7
  • Math expert for every subject
  • Pay only if we can solve it
Ask Question

Answers (2)

Octavio Barr
Answered 2022-07-21 Author has 11 answers
You have for some A and B
2 x 2 1 = 2 ( x 1 ) ( x + 1 ) = A x 1 + B x + 1
You can then calculate A and B by multiplication with x 2 1 and comparison. After that you can simplify it.

We have step-by-step solutions for your answer!

Lorelei Patterson
Answered 2022-07-22 Author has 6 answers
2 x 2 1 + x x + 1 1 x 1 = 2 x 2 1 + x + 1 x + 1 1 x + 1 1 x 1 = 2 x 2 1 + 1 x 1 + x + 1 x 2 1 = 1 2 x + 2 x 2 1 = 1 2 x 1 = x 1 + 2 x + 1 = x + 1 x + 1 = 1

We have step-by-step solutions for your answer!

Expert Community at Your Service

  • Live experts 24/7
  • Questions are typically answered in as fast as 30 minutes
  • Personalized clear answers
Learn more

You might be interested in

asked 2022-04-24
Is it possible to rationalize a denominator containing two cube roots?
The fraction in question is
1212849+1083128491083
And was reached in calculating the solution to x4x1=0. I've tried all the standard methods, including (a+b)(ab)=a2b2, but that doesn't work for cube roots, because once you have the square of one the two middle terms will not cancel each other out.
asked 2021-12-14
How do you convert 0.27 (27 repeating) to a fraction?
asked 2021-10-18
Express 1(3t+1)(t+1) in partial fractions.
By using the substitution t=tanx , or otherwise, show that 0π4dx3+5sin2x=18ln2
asked 2022-06-10
Solving a rational equation with multiple and nested fractions
This is the equation to solve: x + 1 2 1 2 + x 3 1 4 + x 5 = 3
What I did:
x + 1 2 = 2 x + 1 2
x 3 + 1 2 = 2 x + 3 6
x 5 + 1 4 = 4 x + 5 20
2 x + 1 2 ÷ 2 x + 3 6 = 2 x + 1 2 × 6 2 x + 3 = 6 x + 3 2 x + 3
6 x + 3 2 x + 3 ÷ 4 x + 5 20 = 6 x + 3 2 x + 3 × 20 4 x + 5 = 3
120 x + 60 ( 2 x + 3 ) ( 4 x + 5 ) = 3
I know how to solve the equation. But right now I tried several times and I got wrong answers.
So I appreciate your help. Thank you.
asked 2022-04-30
Evaluate 6 5  + 3 5 =?
asked 2022-09-14
Can we divide two terms in finding solution for Linear Inequalities?
Solve the following inequality.
| x 2 | x 2 > 0
If x is greater than or equal to 2, it becomes: x 2 x 2 > 0, which can become 1 > 0, which is true for all x > 2 for when x = 2,its value will become undefined. Is my solution correct?
asked 2022-09-14
I'm trying to prove that the best moment tail bound is no worse than the best Chernoff bound. I have all pieces other than this little frustration here:
If c a i b i i, then c i = 1 a i i = 1 b i

New questions